2010
DOI: 10.1016/j.jaapos.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral reading after treatment of dense congenital unilateral cataract

Abstract: Background Good long-term visual acuity outcomes for children with dense congenital unilateral cataracts have been reported following early surgery and good compliance with postoperative amblyopia therapy. However, treated eyes rarely achieve normal visual acuity and there has been no formal evaluation of the utility of the treated eye for reading. Methods Eighteen children previously treated for dense congenital unilateral cataract were tested monocularly with the Gray Oral Reading Test, 4th edition (GORT-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Amblyopia was very pronounced in this study (mean IAD was 0.58 ± 0.20 logMAR with a median of 0.54 logMAR) in comparison with literature. Birch et al (8) , studied 55 children with unilateral cataract operated untill the 6 weeks of age and observed mean IAD of 0.22 logMAR. Drummond et al (13) evaluated 14 children with unilateral cataract who had surgery before the 17 th week of life, and had an IAD of 0.4 logMAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyopia was very pronounced in this study (mean IAD was 0.58 ± 0.20 logMAR with a median of 0.54 logMAR) in comparison with literature. Birch et al (8) , studied 55 children with unilateral cataract operated untill the 6 weeks of age and observed mean IAD of 0.22 logMAR. Drummond et al (13) evaluated 14 children with unilateral cataract who had surgery before the 17 th week of life, and had an IAD of 0.4 logMAR.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy in the literature regarding the optimal age for surgical removal. Surgery up to 6 weeks of life is believed to provide good outcomes (7)(8)(9) , with a maximum limit until 12 weeks of age (10) . On the other hand, visual acuity of 20/60 could be achieved in uncomplicated cases with surgery in the first 6 months of age (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that treatment initiated at one to six weeks of age maximised the opportunity for normal or near-normal visual development of a congenitally cataractous eye with little or no risk to the phakic fellow eye [96].…”
Section: Cataractsmentioning
confidence: 96%
“…This "reverse occlusion" approach has been validated in animals (11,12) and represents the cornerstone of current treatment (patching therapy) of human amblyopia (13)(14)(15)(16). However, this treatment has well-known limitations that include poor compliance, potential loss of vision through the newly patched eye, failure to recover binocular vision, and a declining treatment efficacy with age (15,(17)(18)(19)(20)(21). Nevertheless, the success of reverse occlusion strategies demonstrates that severely weakened synaptic inputs in the brain can be rejuvenated under appropriate circumstances.…”
mentioning
confidence: 99%